2018
DOI: 10.5006/2788
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Transform Modulus Maxima and Holder Exponents Combined with Transient Detection for the Differentiation of Pitting Corrosion Using Electrochemical Noise

Abstract: A potentially powerful tool to detect and classify corrosion mechanisms is the analysis of electrochemical noise (EN). Data analysis in the time-frequency domain using e.g. continuous wavelet transform (CWT) allows the extraction of localized frequency information, providing information on the type of corrosion, i.e. uniform or localized corrosion, from the EN signal. The CWT provides the opportunity to analyse changes in frequency behavior of electrochemical noise signals over time. In the presence of transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Moreover, Ti alloys do not present damage on the surface [7,77]. Researchers have also found that titanium is not affected by pitting corrosion in salt media when the temperature is under 90 • C, that Cl − ions will not penetrate the surface of alloys, and that the alloy shows passivation [17,46,[78][79][80][81][82][83][84][85].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ti alloys do not present damage on the surface [7,77]. Researchers have also found that titanium is not affected by pitting corrosion in salt media when the temperature is under 90 • C, that Cl − ions will not penetrate the surface of alloys, and that the alloy shows passivation [17,46,[78][79][80][81][82][83][84][85].…”
Section: Discussionmentioning
confidence: 99%
“…The electrochemical potential noise (EPN) monitored in parallel with the optical analysis serves as a basis for the time-frequency electrochemical analysis using CWT as previously shown for steel. 19 The in-situ combination of optical and electrochemical analysis allowed for the first time to directly assign electrochemical signals to specific corrosion processes (e.g. de-alloying, trenching, pitting and oxide formation).…”
mentioning
confidence: 99%
“…to keep the lowest frequency constant. Where applicable, transients in the EPN signals were located using an automated transient analysis technique based on modulus maxima in the CWT spectrum, which was published in earlier work [37] . Modulus maxima effectively indicate the locations of ridges, and therefore singularities or transients, in CWT spectra [37] .…”
Section: Methodsmentioning
confidence: 99%